18. PATTERN OF DISEASE AND OUTCOMES OF TREATMENT AMONG PATIENTS ON MECHANICAL VENTILATION IN PEDIATRIC INTENSIVE CARE UNIT AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the disease and treatment results of mechanically ventilated patients in the pediatric intensive care unit at Nghe An Obstetrics and Pediatrics Hospital.Subjects and research methods: A descriptive cross-sectional study of 200 mechanically ventilated patients in the PICU in 2022.Results: Ventilated children with diseases of the respiratory system (chapter X) accounted for the highest (30%), followed by certain infectious and parasitic diseases (chapter I) accounting for 16%. Diseases of the nervous system (chapter VI), and diseases of the circulatory system (chapter IX) accounted for 10.5% and 9.5%, respectively. In ventilators due to respiratory diseases, pneumonia was the most common, accounting for 73.3%, and pleural effusion and acute respiratory distress syndrome accounted for 6.7%. There were 19 mechanically ventilated patients due to diseases of the cardiovascular system, in which primary hypertension accounted for the highest rate of 31.6%, followed by myocarditis and arrhythmias, both accounting for 21.1%. 21 patients with mechanical ventilation due to nervous system diseases, in which meningoencephalitis did not account for the highest rate of 57.1%, followed by myasthenia gravis took up 23.8%, and epilepsy took up 14.3%. The mortality rate accounted for 49,5%, the survival rate was 37.5%, and the transferred rate to a high level was 13%.Conclusion: The ventilator-associated pattern of the respiratory system and certain infectious and parasitic diseases was high. The mortality rate of ventilator patients is still high.
Keywords: Pattern of disease, outcome, mechanical ventilator.